A physically motivated model based on the strain amplification in filled elastomers. Issue 1 (15th March 2018) - Darabi, Ehsan; Itskov, Mikhail; Klüppel, Manfred
Abstract: A constitutive model for filled elastomers based on a combination of the Dynamic Flocculation Model (DFM) [1] framework and the continuum damage model [2] is proposed. This contribution represents an extension of the previously proposed micro‐mechanical model explaining simultaneously induced filler breakage and polymer‐filler network damage [3]. These effects are attributed to the hydrodynamic strain amplification which is the main topic of the current work. Deformation causes damage in both the network rubbery matrix and inside the filler aggregates. As a result, the probability density function of the number of segments and the filler size distribution change with the strain in all spatial directions which leads to stress softening and the Mullins effect. The model also describes the deformation induced anisotropy and permanent set. A small number of physically motivated material constants describing the average filler cluster dimensions, filler‐filler and filler‐matrix interaction properties are included in the model. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)